2023
DOI: 10.1101/2023.08.29.554603
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ATP13A3Variants Promote Pulmonary Arterial Hypertension by Disrupting Polyamine Transport

Bin Liu,
Mujahid Azfar,
Ekaterina Legchenko
et al.

Abstract: AimsPotential loss-of-function variants ofATP13A3, the gene encoding a P5B-type transport ATPase of undefined function, were recently identified in pulmonary arterial hypertension (PAH) patients. ATP13A3 is implicated in polyamine transport but its function has not been fully elucidated. Here, we sought to determine the biological function of ATP13A3 in vascular endothelial cells and how PAH-associated mutations may contribute to disease pathogenesis. We also generated mice harbouring anAtp13a3variant analogou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Recently, miR-31-5p was reported to be upregulated in the right ventricle of PAH patients, especially in male patients, where its expression was regulated by a network of circular RNAs and lncRNAs [45]. Besides, miR-31-5p could target ATP13A3 , whose haploinsufficiency causes PAH [46,47]. Thus, the implication of this miRNA in PAH pathogenesis make sense if we focus in proliferation/inhibition and how it is reported to interact with vascular smooth muscle cells [41,43], it could help in the overall proliferative environment of PAH-development with enhanced SMC/PAEC/AF proliferation and migration.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, miR-31-5p was reported to be upregulated in the right ventricle of PAH patients, especially in male patients, where its expression was regulated by a network of circular RNAs and lncRNAs [45]. Besides, miR-31-5p could target ATP13A3 , whose haploinsufficiency causes PAH [46,47]. Thus, the implication of this miRNA in PAH pathogenesis make sense if we focus in proliferation/inhibition and how it is reported to interact with vascular smooth muscle cells [41,43], it could help in the overall proliferative environment of PAH-development with enhanced SMC/PAEC/AF proliferation and migration.…”
Section: Discussionmentioning
confidence: 99%
“…The central role of eIF5A in both metabolic and molecular alterations is raising the possibility that Hyp eIF5A serves as a coordinator of metabolic and molecular changes in PAH PASMCs. Furthermore, Hyp eIF5A regulates inflammation and immunity ( 3 ), the deficiency of polyamine transporter ATP13A3 was recently linked to the PA endothelial dysfunction in PAH ( 13 ) ( Figure 1 ), and Lemay and colleagues observed that inhibition of hypusine signaling decreases TGFβ-dependent production of matrix proteins by right ventricular fibroblasts ( 5 ), suggestive of broad multicellular and multiorgan involvement of eIF5A/polyamine metabolism in PAH pathogenesis.…”
mentioning
confidence: 99%